Unlocking the Power of Internal Control: How It Lowers Risk and Slashes Logistics Costs in Retail - Haryanto, Haryanto; Wahjoe Hapsari, Dini; Hidayah, Nurul (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
Effective internal control is crucial for optimizing the logistics process and mitigating potential financial and operational losses associated with various risks, including inventory discrepancies, delayed deliveries, and lost goods. This study examines internal control's role in minimizing logistics risks and costs within the retail sector. This research uses a qualitative approach and a descriptive method, and the findings reveal that internal control is vital for the retail industry, particularly in decreasing operational risks and managing high logistics costs. By implementing standardized procedures, companies can enhance the efficiency of inventory management, distribution, and storage, thereby reducing the likelihood of loss or inaccuracies in stock data. Furthermore, the segregation of duties safeguards against fraud and improves overall accuracy. Internal control also fosters cost-efficiency by optimizing inventory management, employing technology for real-time monitoring of shipments and distribution, and better overseeing transportation budgets. Additionally, it ensures adherence to relevant regulations and legal standards, promotes transparency and accountability within the logistics process, and bolsters the organization's integrity. Thus, internal control significantly contributes to effective risk management, cost efficiency, and the sustainability of businesses in the retail sector.